Workshop on Producing Healthy Meatballs at the PKK Griya Shanta Malang City - Amertaningtyas, Dedes; Nursita, Ita Wahju; Minarti, Sri; Evanuarini, Herly; Maylinda, Sucik; Widati, Aris Sri; Puspita, Poppy Satya; Pangesti, Indha Fitria (Journal of Innovation and Applied Technology, 2026)
This community service activity aimed to improve the knowledge and skills of PKK women members in Malang City regarding the production of healthy, fiber-rich meatballs. The program introduced the use of Eucheuma cottoni as a tapioca substitute and Auricularia nigricans as a functional fiber source to enhance meatball texture and nutritional value. Educational sessions covered ingredients, formulation, processing methods, packaging, and storage techniques. Participants were also introduced to various meatball formulations, including chicken-beef mixtures and 100% beef meatballs. Conducted on May 24, 2025, with 20 participants, the activity resulted in a 10–53% increase in participants’ knowledge based on pre- and post-activity questionnaire analysis